THE EFFECT OF STORE IMAGE, RISK PERCEPTION, AND PRICE PERCEPTION ON CONSUMER BUYING INTEREST IN PRIVATE LABEL PRODUCTS - Bagoes Pambudi; R.A. Marlien (STIE Pelita Nusantara Semarang, 2021)
Alfamart is one of the modern retail companies in Indonesia that has many private label products. In the face of competition between retail businesses, Alfamart continues to expand the manufacture of private label products. This study aims to examine and analyze the effect of store image, risk perception, and price perception on consumer buying interest in private label products. Objects that will be used as respondents in this study are consumers of Alfamart Gringsing in Batang Regency. Purposive sampling method was used for the sampling technique and obtained 120 respondents. The data analysis method uses Multiple Regression that partially store image, risk perception and price perception have a significant effect on buying interest